METHODS OF MORNING GYMNASTICS IN SMALL AND MIDDLE GROUPS AND THEIR SIGNIFICANCE (Scientific journal of the Fergana State University, 2023)
In the article, morning gymnastics in senior and pre-school preparation groups, in addition to the main task, provides an organized start to each day in kindergarten, during self-service and other allows to draw children's attention to cooperative forms of activity. Methods of conducting morning gymnastics in small and medium groups and their importance were studied and analyzed.